Cyberattacks and the Erosion of State Sovereignty - Ana Maria COSTEA; Mihail CARADAICĂ (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
This paper will tackle the issue of cyberattacks and the Erosion of State Sovereignty as cyberattacks have become a significant challenge to state sovereignty in the 21st century, threatening traditional concept of territorial control as well as the modern reliance on digital infrastructure. As technology evolved, cyberattacks developed the ability to bypass national borders and undermine state authority, creating a significant impact on how sovereignty is understood and protected. Considering the theoretical contribution of Carl von Clausewitz on new forms of warfare and Joseph Nye Jr.'s on cyber deterrence, the aim of this paper is to analyze examples such as WannaCry, Stuxnet, SolarWinds, and Heartbleed and to reveal the extent to which cyber operations can erode state sovereignty and challenge international norms.